Observational study of comparison of BISAP score with Ranson’s score and APACHE II scores in assessing severity and prognosis in patients of acute pancreatitis - Modi, Jenish Vijaykumar; Sheth, Jenish (International Surgery Journal, 2018)
Background: Acute pancreatitis is one of the most common diseases of gastrointestinal tract, leading to tremendous emotional, physical and financial burden. Acute pancreatitis is an acute inflammation of the prior normal gland parenchyma which is usually reversible (but acute attack can occur in a pre-existing chronic pancreatitis) with raised pancreatic enzyme levels in blood and urine. It may be first attack or relapsing attacks with an apparently normal gland in between. Biliary tract disease and alcoholism are the commonest cause of pancreatitis. Methods: It was an observational study at Surat municipal institute of medical education and research (SMIMER), Department of Surgery. In present study authors used BISAP score, RANSON’S score and APACHE II score to evaluate the severity and mortality in cases of pancreatitis. In present study authors have compare all the scoring system on the basis of CT scan findings. In present study authors have included all patients above age of 18 years. Patient below 18 years of age, acute on chronic pancreatitis and hereditary pancreatitis were not included. Results: In this retrospective study, we found that incidence of colorectal carcinoma is more between 40-60 years of age with male predominance; lymph node metastasis is more than metastasis in any other sites. CT scan can diagnose lymphatic metastasis and infiltration in surrounding tissue more accurately. Percentage of sphincter saving procedure were low in rectal malignancies in our study. Conclusions: All three-scoring system assess the prognosis of the patient, but the prognosis assessed by APACHE II score is better, but for quick and easy assessment, BISAP score is good for prognosis because APACHE II score uses more parameters to assess the prognosis and BISAP score uses less parameters to assess the prognosis.